Podporządkowanie pracownika nauki w wykonywaniu obowiązku twórczej pracy badawczej - Chobot, Andrzej (Wydział Prawa i Administracji UAM, 1971)
Our considerations contain employees, who are obliged to do a creative research work. Labour law regulations call them the employee (creative workes) of science. Peculiarities of the creative research work are much different from the peculiarities of other works. It is important for the obedience of employee of science in fulfilment the duty of creative research work. The labour law makes dependent a scope and limits of obedience from the peculiarities of the given kind work. Law character of obedience is not strictly defined in science of Polish labour law. We accepted, that obedience is the elementary relation of the competence- -dependence type in a complex legal relationship of employer and employee, arising between employee and amployer, represented by manager, being immediate superior of this employee, in which by doing use with the competence, manager make timely the duty of the employee. In other words, obedience is reduced to deciding by manager in the matter wide understood manner of doing work. Law regulations require a selfrealiance and independence of worker of science in fulfilment the creative research work. After all, law regulations say, that certain categories of employees of science, do the creative research work under a management of other employees of science. We can suppose, that the meaning of management universal received in our labour law don't apply to a management of creative research work. Analysis of the law texts, consisting the creative research work, corroborates this supposing. The peculiarities of this work, require different regulation from the universal received law regulation in our labour law. In connection with this, special kind of management exists, and it is called science management. It has a specific peculiarity. The obedience exists here, but only in much limited scope. It relates only, to operation, making a indispensable condition of information of manager of doing the creative research work. In a remaining scope, the order is replaced by agreement. So the management relies on, as if, a law of veto, which the science manager can put on doing the creative research work. The science management is entirely independent from a management on the ground filling posts in the administrative hierarchy. It can be done only by the science employees, who have formal corroborated, highest science qualifications. It relies on the management of the particular science employee, as well as on the management of the groups of science employees. Particular law regulation of doing the creative research work is substatiated in the light of „praxeology", psychology, physiology and sociology.
The Problem of Employee's Obedience in Fulfilment the Duty of Creative Research Work